Design parameters and environmental impact of printed wiring board manufacture. (20th November 2019) - Alcaraz Ochoa, Maria Lourdes; He, Haoyang; Schoenung, Julie M.; Helminen, Erkko; Okrasinski, Tom; Schaeffer, Bill; Smith, Brian; Davignon, John; Marcanti, Larry; Olivetti, Elsa A.
Abstract: The environmental life cycle impact of electronics continues to be of interest within the life cycle arena. Previous work has shown the majority of burden can be attributed to the use phase as well as the manufacturing impact of components. This study leverages primary data from an industrial facility to provide an assessment of the cradle-to-gate global warming potential for printed wiring board (PWBs) components used in electronics equipment. There has not been as much evolution in the technology for PWBs as compared to other components such as integrated circuits. A newer technology, high-density interconnect (HDI) PWBs, is evaluated in addition to conventional boards based on various representative designs for consumer products. The results show that the board impact for handheld devices, notebooks and desktops range from to around 0.6 to 10 kgCO2 e/board. The cradle-to-gate global warming potential is dominated by the manufacturing energy to fabricate the board as well as the board laminate materials (80% of the total impact). The study demonstrates that environmental impact varies by design parameters other than layer count and board area. The research also assesses the water use and chemical hazard associated with PWB manufacture. Highlights: We analyze global warming, water, and chemical use for printed wiring boards. Variation of impact with design of high density interconnect boards. Impact driven by energy to fabricate boards and board laminate materials.